MEDIA DISCOURSE AS SEMIOSIS: THE POTENTIAL OF SEMIOTICS FOR DEFINING MEDIA DISCOURSE - TSARYK, Halyna (Linguistic and Conceptual Worldviews, 2024)
Background. Discourse theory is interdisciplinary. The methodological apparatus of linguistics and various related fields such as sociology, culturology, psychology, and linguosemiotics, is applied to study, comprehend, interpret, and formulate the methodological principles of discourse analysis (including media discourse as a subtype of institutional discourse) and its components (text, utterance, communicative event, communicative act). Methods and approaches to studying media discourse mostly complement each other, thus being participatory. At the current stage of language science development, media discourse is the object of numerous research investigations by Ukrainian and foreign linguists. The article aims to propose a definition of media discourse by identifying its key features as a category of communication generated by mass media. To achieve this purpose: • a) we consider media discourse as a complex sign and analyze its action of sign (semiosis); • b) with a focus on the sociosemiosic approach to discourse analysis, we identify characteristic features of this discourse and define it as a subtype of institutional discourse; • c) we provide an interpretation of the main metalanguage units used to describe the proposed approach. Methods. The research has been conducted based on the methodological principles developed in modern communicative linguistics using a semiosic approach to discourse analysis. To achieve the research aim, the following general scientific methods are applied: descriptive, inductive, comparative, generalization, and a special method of linguistic semiotic discourse interpretation. Results. Media discourse (MD) is characterized by the following features: • Generated by various agents (including media producers — institutions and individuals — and recipients). • Comprises a variety of speech genres embodied in texts, which are complex signs, the signification of which is characterized by code, information and cultural dimensions. • Directed towards interaction. The core finding of our investigation is considered to be the reasoned presentation of the effectiveness of applying a semiotic approach to the analysis of media discourse. Conclusion. Media discourse is a complex sign, the signification of which occurs in the informational space and is characterized by code, informational, and cultural dimensions